Implementation of Digital-Based Learning in Islamic Religious Education Subjects - Rahmat Saputra (EDUJAVARE: International Journal of Educational Research, 2026)
The increasingly rapid development of information and communication technology has brought significant changes to various aspects of life, including education. This study aims to analyze the implementation of digital-based learning in Islamic Religious Education (PAI) and identify the impacts and obstacles encountered in its implementation. This study uses a qualitative, descriptive approach. The research subjects included PAI teachers, students, and relevant stakeholders within the school environment. Data collection techniques were conducted through observation, interviews, and documentation. Data analysis was conducted interactively through the stages of data reduction, data presentation, and conclusion drawing, and its validity was tested through triangulation of sources and methods. The results show that the implementation of digital-based learning in PAI has a positive impact on increasing student motivation, interest, and learning outcomes. The use of digital media such as learning videos, e-learning platforms, and interactive applications can create a more engaging, flexible, and effective learning environment. In addition, digital-based learning also encourages independent learning and increases active student participation in the learning process. However, several obstacles remain in its implementation, including limited technological facilities, unequal internet access, and teachers' digital competencies that still need to be improved.